Optimally cloned binary coherent states - Müller, Christian; Leuchs, Gerd; Marquardt, Christoph; Andersen, U. L. (Physical Review A, 2017)
Binary coherent state alphabets can be represented in a two-dimensional Hilbert space. We capitalize this formal connection between the otherwise distinct domains of qubits and continuous variable states to map binary phase-shift keyed coherent states onto the Bloch sphere and to derive their quantum-optimal clones. We analyze the Wigner function and the cumulants of the clones, and we conclude that optimal cloning of binary coherent states requires a nonlinearity above second order. We propose several practical and near-optimal cloning schemes and compare their cloning fidelity to the optimal cloner.
CRIS-Team Scopus Importer:2022-06-05